Student perceptions and trust of sustainability information. Issue 4 (7th May 2019) - Hay, Rachel; Eagle, Lynne; Saleem, Muhammad Abid; Vandommele, Lisa; Li, Siqiwen
Abstract : Purpose: The purpose of this paper is to report student attitudes and beliefs towards climate change adaptation and sustainability-related behaviours. Design/methodology/approach: A paper-based questionnaire was completed by 247 first-year (students in their first semester of study) and third-year (students in their final semester of study) students in the same year (2012) of the study (Table I). A factor analysis shows that common themes previously identified failed to reflect the diverse range of influences on young people, including family, friends and news media. Findings: Contrary to the literature, few significant differences were found in sustainability-related behaviours between first- and third-semester students, with an increase in scepticism regarding the reality of climate change among the latter. Research limitations/implications: The study focused on Australian undergraduate university business students. As a single-institution case study, the results may not be generalised to all university students. As such the authors recommended that the study be completed in other universities from around the world. The study was undertaken over one year, but the participants may not have necessarily been the same students in third semester as they were in first semester. Therefore, it is recommended that the study be repeated in future years so that the same cohort can be measured over time, providing a more accurate account of the development of student knowledge and perceptions of sustainability during their time at university. Practical implications: Achieving significant long-term changes in behaviours will be a substantial challenge for tertiary curricula. The findings of this study can inform instructors in higher education of student attitudes towards sustainability and climate change adaption and in turn inform changes to tertiary curriculum in sustainability and climate change adaption. Originality/value: This paper reports on the second phase of a longitudinal research project examining the effects of an undergraduate business studies curriculum on student views of sustainability. The authors confirm that the research is original and that all of the data provided in the study are real and authentic. Neither the entire work nor any of its parts have been previously published.